Redefining trade promotion : the need for a strategic response - International Trade Centre; Executive Forum on National Export Startegies (Geneva International Trade Centre, 2000)
Summary of discussions held at the Executive Forum on National Export Strategies, organized by International Trade Center, Annecy, France, 26-29 September 1999 - Assesses what a national export strategy should encompass with the regard to dynamics of current international market environment; looks at process of strategy development and management, reviewing basic questions of leadership and ownership; examines types of institutional linkages and functional relationship required for effective formulation and implementation of broad-based strategies; reviews techniques and issues related to utility and impact assessment of national export strategies; explores implications of electronic commerce, increasing dominance of multinationals, and global outsourcing for national export strategies.
Foreword -- Acknowledgments -- Notes -- Introduction -- Chapter 1 : a call to redefine trade promotion -- Strategic challenge 1: balancing needs -- Strategic challenge 2: Need vs. demand -- Strategic challenge 3: Total competitiveness response capacity -- Strategic challenge 4: Who is the client? -- Strategic challenge 5: Coming onshore to promote new capacities -- Strategic challenge 6: Generating synergies -- Strategic challenge 7: Lowering the cost of doing business -- Strategic challenge 8: shortcutting the internationalization process -- Strategic challenge 9: Reorienting trade promotion to develop long-term relationships -- Strategic challenge 10: Promoting foreign direct investments -- Chapter 2 : initiating the process -- The strategic response -- Building capacity for better understanding of the market -- Moving up the value chain -- Improving the national competitiveness environment -- Chapter 3 : strategic linkages -- Planning and consensus-building linkages -- Implementation and efficiency-building linkages -- Performance monitoring and assessment linkages -- Mandating linkages -- Promoting informal national networks -- Promoting private-sector linkages -- Developing functional linkages -- Chapter 4 : rethinking evaluation -- Evaluating programmes -- Evaluating providers -- Evaluating strategies at the macroeconomic level -- An enterprise-focused approach to evolution -- A strategic approach to evaluation -- Chapter 5 : drivers of competitiveness -- Competitiveness driver 1: priority of rapid response -- Competitiveness driver 2: Globalization of the supply chain -- Competitiveness driver 3: increasing importance of the product's service envelope -- A final word: the public sector's influence over business competitiveness --
At head of title : International Trade Centre, Executive Forum
Keywords: International Trade; FOREIGN TRADE; INTERNATIONAL TRADE; TRADE PROMOTION; EXPORT PROMOTION; EVALUATION; STRATEGIC PLANNING